Development of Ludo Pintar Indonesian Language Learning Media to Increase Student Learning Motivation in Elementary Madrasahs - Ulfatur Rizko; Samsul Susilawati; Bintoro Widodo (Journal of Educational Sciences, 2026)
This study aims to improve students' learning motivation in Indonesian language learning through the development of the Ludo Pintar media. The background of this study is the low learning motivation of students at MI Ihyaul Islam I, Probolinggo Regency, which is caused by the dominant use of lecture and practice methods, which makes students passive and easily bored. The Ludo Pintar media is designed as a fun educational game to help students understand synonyms and antonyms interactively. This study uses the ADDIE development model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects involved media experts, material experts, teachers, and fifth grade students. Data were collected through interviews, observations, questionnaires, and documentation. The validation results showed that the media was declared very valid by media experts (86%) and valid by material experts (73%). The practicality test obtained a teacher response of 91%, indicating that the media is very easy to use and interesting. In addition, the results of the effectiveness test showed an increase in learning motivation from an average of 29.33 to 51, with an increase of 74%. Thus, the Ludo Pintar media is feasible, practical, and effective for use in Indonesian language learning in elementary schools.